Estudo de equivalência farmacêutica dos fármacos captopril e cloridrato de propranolol comercializados no programa farmácia popular do Brasil - Pontes, Andréa Vieira (2009)
The pharmaceutical equivalence between two medicines is based on the confirmation that both contain the same active drug on the same dosage and dosage form, wich is assessed by in vitro tests. In Brazil, the National Health Surveillance Agency defines that allopathic medicines can be registered in three categories: innovator, generic and similar drugs. The actual legislation determines that to register new generic and similar medicines it is necessary to prove its pharmaceutical equivalence and bioequivalence with a reference drug. Products registered before 2003 have until 2014 to present these equivalence results. The Popular Pharmacy Program in Brazil is a new strategy of pharmaceutical assistance of the Health Sistem with the purpose to facilitate the population’s access to medicines considered basic and essential, lowering the price impact of these medicines in the family budgets. The objective of this study was to assess the pharmaceutical equivalence of captopril 25 mg and propranolol hydrochloride 40 mg tablets sold in the Popular Pharmacy Program in Brazil, comparing them to a reference and generic drug, debating the importance of the quality of drugs for the public health. Physical and physicochemical tests such as identification, weight variation, disintegration, hardness, friability, purity, dosage, content uniformity, and dissolution profile, were performed according to the Brazillian Pharmacopeia 4th edition. The results showed a low hardness of propranolol hydrochloride tablets originated from the Popular Pharmacy Program. The dissolution profiles analised by analysis of variance (ANOVA) and Tukey test demonstrated significant differences between the dissolution profiles of both drugs originated from the Popular Pharmacy Program and their respective reference and generic drugs (p<0,001). The dissolution profiles were compared by the Dissolution Efficiency method. The extention of the active drug dissolved from the Popular Pharmacy medicine was significantly lower than the dissolution from the reference and generic drugs (P < 0,001) for both captopril and propranolol hydrochloride. Even though captopril would fulfill the requirements of the National Health Surveillance Agency to be considered equivalent, it was not approved on the dissolution efficiency test. Therefore, the assessed tablets originated from the Popular Pharmacy Program in Brazil were not considered pharmaceutical equivalents when compared to their respective reference and generic drugs.